Emission characteristics of palm oil shell in a cascading hearth staged combustor / Wan Ahmad Najmi Wan Mohamed - Wan Mohamed, Wan Ahmad Najmi (UPENA, 2004)
Palm oil shells are biomass fuels with 47.62% carbon and 0.7% nitrogen content, and a higher heating value of 20.7 MJIkg. This paper investigates the emission characteristics of CO and NOt from the thermal processing of palm oil shells in a cascading hearth staged combustor. The cascading hearths in primary staged combustion offers higher solids burnout rate by the action of fuel movement and distribution. Secondary stage applies swirl flow combustion to enhance efficiency in pollution control. The experimental is conducted at 0.2 kg/min fuel feed, and primary stage air is supplied at starved and excess conditions. Comparative analysis is conducted in understanding the combustion and emission characteristics under both conditions. Starved air is found to lower primary combustion temperatures (400°C - 900°C), and gasification is promoted which leads to high carbon monoxide levels (1800 - 3400ppm). Secondary stage combustion furthers the oxidation of CO to C02 at an approximated oxidation efficiency of 70%, with flue gas CO measured at 600 - 800ppm. NOt levels were successfully controlled below WOppm due to moderate combustion temperatures achieved in both combustion stages (300°C to 700°C).